RANCANG BANGUN APLIKASI SMS GATEWAY UNTUK PEMESANAN TIKET BUS (Information Technology and Telematics, 2013)
Applications sms gateway service using SMS (Short Message Service) is a technology services for the delivery of short messages. Penchant for the mobile users to SMS are cheaper, practical and present in all kinds and types of mobile phones, making this one feature is widely used in the business sector. Agent Bus Pahala Kencana is one bus ticket booking which has quite a lot of customers. Development of information systems based on bus ticket booking sms gateway is designed to enable customers to access bus ticket booking information. This application uses the methodology of system development life cycle has five stages perancanaan, analysis, design, implementation and evaluation. The programming language used is PHP, using a MySQL database storage and SMS gateway using Gammu Engine. The system bus ticket booking information will be reply any SMS sent by the customer in accordance with a predetermined SMS format. The system will also accommodate SMS suggestions or criticisms and report to the director within a certain timeframe. The benefits of the design of this system is to help customers Agent Bus Pahala Kencana in obtaining a bus ticket booking information no matter where the customer is for mobile operators in the area itself. Another benefit is to improve the quality of service of Agent Bus Pahala Kencana to its customers based on inputs that come from customers. Keywords: SMS (Short Message Service), system development life cycle, Engine SMS Gateway, Gammu.